2020
DOI: 10.1093/cvr/cvaa284
|View full text |Cite
|
Sign up to set email alerts
|

Higher mortality of COVID-19 in males: sex differences in immune response and cardiovascular comorbidities

Abstract: The high mortality rate of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection is a critical concern of the Coronavirus Disease 2019 (COVID-19) pandemic. Strikingly, men account for the majority of COVID-19 deaths, with current figures ranging from 59–75% of total mortality. However, despite clear implications in relation to COVID-19 mortality, most research has not considered sex as a critical factor in data analysis. Here, we highlight fundamental biological differences that exist between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
194
5
18

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(262 citation statements)
references
References 137 publications
19
194
5
18
Order By: Relevance
“…Of interest, in addition to trajectories over the life course for BP, 81 aging might thus also differentially affect the immunoinflammation status in patients with hypertension. In this regard, as recently indicated, 82 a sexual dimorphism affecting both the innate and adaptive immune system could contribute to the higher mortality risk of male patients 4 in COVID-19, particularly in the context of hypertension with inherent dysregulated immunoinflammation.…”
Section: Sars-cov-2 Responses In Airway Cells and Hypertensionmentioning
confidence: 84%
“…Of interest, in addition to trajectories over the life course for BP, 81 aging might thus also differentially affect the immunoinflammation status in patients with hypertension. In this regard, as recently indicated, 82 a sexual dimorphism affecting both the innate and adaptive immune system could contribute to the higher mortality risk of male patients 4 in COVID-19, particularly in the context of hypertension with inherent dysregulated immunoinflammation.…”
Section: Sars-cov-2 Responses In Airway Cells and Hypertensionmentioning
confidence: 84%
“…The kidney organoids we used were of female origin, and ideally, one should examine this model originating from both sexes to consider that ACE2 is on the X chromosome and that in clinical studies, men appear more susceptible for severe COVID-19. 35 Studies in adult organoids, moreover, would also be important to better replicate the mature human kidney. Therefore, it would be important to test ACE2 treatment and SARS-CoV-2 in three-dimensional kidney spheroids/organoids of adult origin harboring mature phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the different mortality rates in COVID-19 patients is due to the difference in the response to infection ( Bienvenu et al., 2020 ). Analysis of viral RNA in COVID-19 patients indicated that the males show delayed viral clearance ( Xu K. et al., 2020 ; Zheng S. et al., 2020 ).…”
Section: Cellular and Molecular Mechanisms Of Diseasementioning
confidence: 99%